The rights of asylum seekers at the external borders of the European Union - Tuisuzova, Irina (Riga Graduate School of Law, 2023)
In my work, I paid attention to asylum seekers in the territory controlled by the European Union. Examined the detention of asylum seekers and recent cases heard by the European Court of Human Rights, as well as the wrongful return of migrants from the borders of the European Union and the application of the principle of non-refoulement. Considered variations in the behaviour of border guards at the borders of the European Union and EU-controlled external territories. In my work, I used the doctrinal research method, which helped me to analyse the legislation of the European Union in the field of migration law and asylum.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Asylum seekers